Corrosion and Wear Properties of Cu-TiC Composites Produced by Hot Pressing Technique - AKKAŞ, Mehmet; ISLAK, Serkan; ÖZORAK, Cihan (Celal Bayar University Journal of Science, 2018)
Cu-xTiC (x=0, 1, 5, 10 and 15 wt.%) composites were prepared by hot pressing (HP) technique. The microstructure, corrosion and wear features of Cu matrix composites (CMCs) were investigated. The wear surfaces and microstructure of the CMCs were analyzed using SEM-EDS. Phases of samples were identified by means of XRD. Hardness measurements of the composites were made using a microhardness device. Hardness tests showed that the hardness tends to increase with increasing TiC amount. Wear properties of the CMCs were determined using ball-on-disc method. Significant decreases in wear rates were observed in composites reinforced with TiC. The corrosion properties of the composites were characterized by potentiostatic polarization test. Corrosion results showed that the corrosion resistance of the composites decreased with the increase of TiC content in Cu. Among the composites, Cu-1% TiC has the best corrosion resistance.
Keywords: Engineering; Mühendislik; Cu/TiC composite; hot press; wear; corrosion; 8. Economic growth